2012
DOI: 10.1084/jem.20102660
|View full text |Cite
|
Sign up to set email alerts
|

Wheat amylase trypsin inhibitors drive intestinal inflammation via activation of toll-like receptor 4

Abstract: Pest resistance molecules, α-amylase/trypsin inhibitors from wheat, activate innate immune cells through engagement of TLR4 to elicit inflammatory responses in the intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
535
0
24

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(575 citation statements)
references
References 48 publications
16
535
0
24
Order By: Relevance
“…Both CXCR3 and TLR4 are expressed on beta cells [46,47] and subsets of NK cells [45,48], and gliadin is known to interact with both receptors [47,49]. Interestingly, a recent study has shown that amylase/trypsin inhibitor family members present in the ω-gliadin fraction are able to induce strong innate responses in human and murine macrophages, monocytes, and DCs via TLR4 [49], through a mechanism that could potentially induce IFN-γ secretion from NK cells [45].We also investigated the effect of gliadins directly on beta cells. C57BL/6 islets incubated with gliadin increase production of insulin, IL-6, and the chemokine CCL2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both CXCR3 and TLR4 are expressed on beta cells [46,47] and subsets of NK cells [45,48], and gliadin is known to interact with both receptors [47,49]. Interestingly, a recent study has shown that amylase/trypsin inhibitor family members present in the ω-gliadin fraction are able to induce strong innate responses in human and murine macrophages, monocytes, and DCs via TLR4 [49], through a mechanism that could potentially induce IFN-γ secretion from NK cells [45].We also investigated the effect of gliadins directly on beta cells. C57BL/6 islets incubated with gliadin increase production of insulin, IL-6, and the chemokine CCL2.…”
mentioning
confidence: 99%
“…Both T1D and CD are multifactorial diseases, where genetic predisposition and the mode, timing, and dose of gluten introduction are important for the development [58]. Most people thus tolerate gluten even if several immune stimulating effects have been described in healthy BALB/c and C57BL/6 mice [11,49,59]. Interestingly, a disorder called nonceliac gluten sensitivity has been described, reporting about a growing number of cases of self-diagnosed patients who observe improvements in several parameters after reducing gluten intake [60].…”
mentioning
confidence: 99%
“…In NCGS patients, gliadin fractions do not provoke a clear picture of inflammation upon contact with the duodenal mucosa or with peripheral basophils [20]. In vitro studies suggest that wheat ATIs could play a major role as triggers of the innate immune response in GS [21].…”
Section: Pathogenesismentioning
confidence: 99%
“…In this respect, it would be interesting to know whether CLE findings correlate with the eosinophil cationic protein concentrations in the stools or with the flow cytometric allergen stimulation assay results, biomarkers that showed a good concordance with the DBPC challenge results in IBS patients. 6,7 …”
mentioning
confidence: 99%